Model Sistem Dinamik Ketersediaan Lahan Terbangun di Provinsi Bengkulu - Budiman Sakti (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2020)
The high population growth rate of Bengkulu Province compared to national population growth resulted in the phenomenon of reduced land availability in Bengkulu Province. This problem is understood and modeled into the Causal Loop Diagram (CLD), then to simulate the system that has been poured into the CLD diagram model, poured into the Stock Flow Diagram (SFD) using Powersim Studio 10 software which is then tested by Average Mean Error (AME). The study area is predicted to reach 50% of the developed land in 2060, then 60% of the developed land is in 2065 and reaches the environmental carrying capacity threshold that is 70% of the developed land in 2070. The developed land develops beyond the threshold that is 80% of the developed land is predicted to occur in 2076 and 90% of the developed land is predicted to occur in 2085. In line with the increase in built-up land and population, economic activity is also increasing due to high community needs, but on the other hand land availability is decreasing to encourage economic growth.